Mechanistic insights into PFAS-induced effects on B lymphocyte activation and antibody secretion - Martina Iulini; Karsten Beekmann; Ron L. A. P. Hoogenboom; Valentina Galbiati; Giulia Russo; Francesco Pappalardo; Styliani Fragki; Alicia Paini; Emanuela Corsini; Aafke W. F. Janssen (Archives of Toxicology, 2026)

An integrated in vitro and in silico testing strategy applied to PFAS inhibition of antibody production to define a tolerable daily intake - Martina Iulini; Aafke W.F. Janssen; Karsten Beekmann; Giulia Russo; Francesco Pappalardo; Styliani Fragki; Alicia Paini; Emanuela Corsini (Toxicology Letters, 2026)

In vitro approaches to investigate the effect of chemicals on antibody production: the case study of PFASs - Martina Iulini; Valeria Bettinsoli; Ambra Maddalon; Valentina Galbiati; Aafke W. F. Janssen; Karsten Beekmann; Giulia Russo; Francesco Pappalardo; Styliani Fragki; Alicia Paini; Emanuela Corsini (Archives of Toxicology, 2025)
The increasing variety and quantity of new chemical substances have raised concerns about their potential immunotoxic effects, making it essential to assess their impact on human health. One key concern is the reduction of antibody production, as seen with per- and poly-fluoroalkyl substances (PFASs), commonly known as “forever chemicals.” Both in vivo and epidemiological data show that PFASs have immunosuppressive effects, leading to reduced antibody responses, particularly following vaccination. In animal studies, the T cell-dependent (TD) antibody response is the gold standard for assessing chemical effects on immune function. This study utilized two in vitro approaches to investigate the effects of chemicals on antibody production using human peripheral blood mononuclear cells. Initial tests used unstimulated, negative (vehicle), and positive (rapamycin) controls to confirm the robustness of the models. Subsequently, four long-chain PFASs (PFOA, PFOS, PFNA, and PFHxS) were tested. Keyhole limpet hemocyanin (KLH) was used to mimic the TD response, while a TLR9 agonist and IL-2 activated B cells for T cell-independent (TI) immunoglobulin production. The results demonstrated the ability to reproduce TD and TI responses in vitro with robust, reproducible outcomes across a cohort of 20 human donors. The data, consistent with existing literature, showed a significant reduction in anti-KLH IgM production, especially for PFOA in male donors. Similar trends were observed for all PFASs in suppressing total TI IgG and IgM production. These methods closely replicated in vivo conditions, offering a potential alternative to animal models in immunotoxicity assessments.

Determination of in vitro hepatotoxic potencies of a series of perfluoroalkyl substances (PFASs) based on gene expression changes in HepaRG liver cells - Jochem Louisse; Styliani Fragki; Deborah Rijkers; Aafke Janssen; Bas van Dijk; Liz Leenders; Martijn Staats; Bas Bokkers; Marco Zeilmaker; Aldert Piersma; Mirjam Luijten; Ron Hoogenboom; et al. (Archives of Toxicology, 2023)
Per- and polyfluoroalkyl substances (PFASs) are omnipresent and have been shown to induce a wide range of adverse health effects, including hepatotoxicity, developmental toxicity, and immunotoxicity. The aim of the present work was to assess whether human HepaRG liver cells can be used to obtain insight into differences in hepatotoxic potencies of a series of PFASs. Therefore, the effects of 18 PFASs on cellular triglyceride accumulation (AdipoRed assay) and gene expression (DNA microarray for PFOS and RT-qPCR for all 18 PFASs) were studied in HepaRG cells. BMDExpress analysis of the PFOS microarray data indicated that various cellular processes were affected at the gene expression level. From these data, ten genes were selected to assess the concentration–effect relationship of all 18 PFASs using RT-qPCR analysis. The AdipoRed data and the RT-qPCR data were used for the derivation of in vitro relative potencies using PROAST analysis. In vitro relative potency factors (RPFs) could be obtained for 8 PFASs (including index chemical PFOA) based on the AdipoRed data, whereas for the selected genes, in vitro RPFs could be obtained for 11–18 PFASs (including index chemical PFOA). For the readout OAT5 expression, in vitro RPFs were obtained for all PFASs. In vitro RPFs were found to correlate in general well with each other (Spearman correlation) except for the PPAR target genes ANGPTL4 and PDK4 . Comparison of in vitro RPFs with RPFs obtained from in vivo studies in rats indicate that best correlations (Spearman correlation) were obtained for in vitro RPFs based on OAT5 and CXCL10 expression changes and external in vivo RPFs. HFPO-TA was found to be the most potent PFAS tested, being around tenfold more potent than PFOA. Altogether, it may be concluded that the HepaRG model may provide relevant data to provide insight into which PFASs are relevant regarding their hepatotoxic effects and that it can be applied as a screening tool to prioritize other PFASs for further hazard and risk assessment.

New approach methodologies: A quantitative in vitro to in vivo extrapolation case study with PFASs - Styliani Fragki; Jochem Louisse; Bas Bokkers; Mirjam Luijten; Ad Peijnenburg; Deborah Rijkers; Aldert H. Piersma; Marco J. Zeilmaker (Food and Chemical Toxicology, 2023)

Towards best use and regulatory acceptance of generic physiologically based kinetic (PBK) models for in vitro-to-in vivo extrapolation (IVIVE) in chemical risk assessment - Abdulkarim Najjar; Ans Punt; John Wambaugh; Alicia Paini; Corie Ellison; Styliani Fragki; Enrica Bianchi; Fagen Zhang; Joost Westerhout; Dennis Mueller; Hequn Li; Quan Shi; et al. (Archives of Toxicology, 2022)
With an increasing need to incorporate new approach methodologies (NAMs) in chemical risk assessment and the concomitant need to phase out animal testing, the interpretation of in vitro assay readouts for quantitative hazard characterisation becomes more important. Physiologically based kinetic (PBK) models, which simulate the fate of chemicals in tissues of the body, play an essential role in extrapolating in vitro effect concentrations to in vivo bioequivalent exposures. As PBK-based testing approaches evolve, it will become essential to standardise PBK modelling approaches towards a consensus approach that can be used in quantitative in vitro-to-in vivo extrapolation (QIVIVE) studies for regulatory chemical risk assessment based on in vitro assays. Based on results of an ECETOC expert workshop, steps are recommended that can improve regulatory adoption: (1) define context and implementation, taking into consideration model complexity for building fit-for-purpose PBK models, (2) harmonise physiological input parameters and their distribution and define criteria for quality chemical-specific parameters, especially in the absence of in vivo data, (3) apply Good Modelling Practices (GMP) to achieve transparency and design a stepwise approach for PBK model development for risk assessors, (4) evaluate model predictions using alternatives to in vivo PK data including read-across approaches, (5) use case studies to facilitate discussions between modellers and regulators of chemical risk assessment. Proof-of-concepts of generic PBK modelling approaches are published in the scientific literature at an increasing rate. Working on the previously proposed steps is, therefore, needed to gain confidence in PBK modelling approaches for regulatory use.